2018
DOI: 10.4269/ajtmh.17-0816
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Trypanosoma cruzi Infection in Salivary Gland of Bats from the Peruvian Amazon

Abstract: Abstract.In the Americas, 8 million people are infected with Chagas disease, and an additional 90 million people are at risk for infection. Little is known about the role bats play in the sylvatic transmission cycle of Trypanosoma cruzi, the parasite causing Chagas disease. Here, we captured bats in the villages of Palmiche, Pachacutec, Nuevo San Martin, and Mayuriaga located in the Datem del Marañon Province in Loreto, Peru. Venous blood samples were collected by cardiac puncture or from the upper extremities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
1
19
0
1
Order By: Relevance
“…Although T. cruzi has been documented in the salivary glands of D. youngi (Villena et al, 2018), our findings comprise the first evidence of TcI in the saliva of D. rotundus and D. ecaudata, two vampire bat species which are known to feed on humans (Ito et al, 2016).…”
Section: Materials S and Me Thodsmentioning
confidence: 55%
See 1 more Smart Citation
“…Although T. cruzi has been documented in the salivary glands of D. youngi (Villena et al, 2018), our findings comprise the first evidence of TcI in the saliva of D. rotundus and D. ecaudata, two vampire bat species which are known to feed on humans (Ito et al, 2016).…”
Section: Materials S and Me Thodsmentioning
confidence: 55%
“…The recent detection of T. cruzi in the salivary glands of Diaemus youngi, a hematophagous bat, suggests the possibility that bats could also act as both reservoirs and transmitters of the parasite (Villena et al, 2018). Bats are important trypanosome reservoirs which host both generalist and bat-restricted trypanosomes (Marcili et al, 2009;Ramírez et al, 2014) and have been suggested as the ancestral host of trypanosomes (Hamilton et al, 2012).…”
mentioning
confidence: 99%
“…The highest infection rate was found in the Amazon basin compared to other biomes, suggesting that unaltered areas nurture a high parasite diversity [9]. In the Peruvian Amazon, a 4.1% T. cruzi infection prevalence in bats was reported, in both hematophagous (2.7%; 2/73) and non-hematophagous species (6.2%; 3/48) [35]. Interestingly, T. cruzi DNA was detected in the salivary glands of Diaemus youngi, an hematophagous bat [35].…”
Section: Quiropteramentioning
confidence: 96%
“…In the Peruvian Amazon, a 4.1% T. cruzi infection prevalence in bats was reported, in both hematophagous (2.7%; 2/73) and non-hematophagous species (6.2%; 3/48) [35]. Interestingly, T. cruzi DNA was detected in the salivary glands of Diaemus youngi, an hematophagous bat [35]. This highlights the importance of studying the transmission mechanisms of T. cruzi in bats and their public health implications for the Amazon basin.…”
Section: Quiropteramentioning
confidence: 99%
“…Se han documentado importantes nuevos y antiguos patógenos en murciélagos hematófagos de nuestra selva, y tenemos los reportes más altos de mordeduras a humanos en el mundo (20)(21)(22)(23) . Para el público en general, no es muy conocido el hecho de que cada una de estas mordeduras resulta en un contacto de al menos 15 minutos piel a piel, y de boca y lengua del murciélago a una herida abierta en un ser humano, frecuentemente cabeza y cara, por lo que el riesgo de que ocurra un evento zoonótico con origen en esta exposición es alto (24) .…”
unclassified